Comparison of Biochemical and Hematological Parameters Among COVID-19 Patients With and Without Vaccination in a Tertiary Care Hospital: A Retrospective - Mahalaxmi S Petimani; Prabhakar Adake; Pavithra H; Drisya Kaladharan (Pharmaceutical and Biomedical Research, 2023)
Background: The availability of the COVID-19 vaccine during the pandemic has changed the disease course in the entire world. The current study aimed to compare various hematological parameters among COVID-19 patients with and without vaccination. Methods: The present retrospective study included 26 vaccinated and 26 non-vaccinated COVID-19 patients. Various clinical and biochemical parameters of RT-PCR-positive patients were collected. The values are expressed in Mean±SD or median values IQR. Mann-Whitney U test was used for comparison between the groups. Results: Among the vaccinated individuals, 17 cases (65.4%) were asymptomatic, one patient (3.8%) had moderate, eight cases (30.8%) had mild COVID-19 infection and all 26 patients were completely recovered. Among non-vaccinated COVID-19 patients, 25 cases (96.2%) had severe, one case (3.8%) had moderate COVID-19, and 16 patients (61.5%) recovered but ten cases succumbed to COVID-19. There were statistically significant differences in SpO2, total leucocyte count, and differential counts of neutrophils, lymphocytes, eosinophils, monocytes, and basophils between vaccinated and non-vaccinated patients (P<0.001). The neutrophil/lymphocyte ratio was found to be at a higher level (P<0.01) among non-vaccinated patients [10.9(4.28-23.63)]  compared to vaccinated [1.55(1.09-2.28)]. The blood urea, total and direct bilirubin, serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), and inflammatory markers, like C-reactive protein (CRP), D-dimer, ferritin, and lactate dehydrogenase (LDH) were highly elevated in non-vaccinated patients (P<0.001). Moreover, lower values of total protein, serum albumin, and albumin and globulin (A/G) ratio were noted in the non-vaccinated compared to vaccinated individuals (P<0.001). Conclusion: Vaccinated patients had milder disease with fewer derangements of hematological parameters compared to non-vaccinated patients. It can be concluded that vaccine has played a vital role during the COVID-19 pandemic in reducing mortality.